CHATGPT: A DOUBLE-EDGED SWORD IN CYBERSECURITY - EVALUATING RISKS AND RECOMMENDATIONS FOR SAFER AI INTEGRATION - Patel, Mitesh G; Prajapati, Hinal N; Patel, Nihar K; Patel, Nirmal S; Patel, Anand K; Brahmbhatt, Hemali A (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Over the years, natural language processing (NLP) has seen remarkable progress, largely thanks to the advancements in artificial intelligence (AI). Specifically, recent strides in this field can be attributed to the emergence of sophisticated conversational AI systems like ChatGPT. Since its release in November 2022, ChatGPT has captivated millions of users with its impressive features and capabilities. However, there’s a growing concern about its potential misuse by malicious actors. In particular, ChatGPT opens up new avenues for hackers to compromise cybersecurity. This article delves into a comprehensive exploration of how ChatGPT can significantly aid hackers in executing various attacks. The investigation draws from cutting-edge research in this domain. Additionally, we evaluate ChatGPT’s impact on cybersecurity, both positive and negative. The conclusion is clear: ChatGPT has indeed facilitated hacking behaviors and could be exploited for malicious purposes. To mitigate these risks, continuous development and the establishment of appropriate standards are crucial. Policymakers and developers must collaborate, taking into account user concerns and the responsible use of this powerful tool. Ultimately, this research article offers insightful discussions and recommendations to enhance AIbased systems.